Association of microalbuminuria in non-diabetic and non-hypertensive patients with myocardial infarction - Basu, Abhijit; Jhala, Jaswant Singh (International Journal of Advances in Medicine, 2017)
Background: This study was designed to evaluate the association of microalbuminuria in non-diabetic and non-hypertensive patients with myocardial infarction and to determine whether microalbuminuria is an independent marker of Myocardial Infarction in non-diabetic and non-hypertensive patients. Methods: This study was conducted over 50 patients diagnosed as ST-segment elevation acute myocardial infarction on the basis of clinical history, examination, ECG changes, & biochemical markers. Cases were selected from a tertiary care hospital, Udaipur. Results: In our study out of the 50 cases 66% (n=33) had microalbuminuria. The difference was statistically significant P <0.001. Microalbuminuria was found in a lower age group (48.76 ± 6.97) in cases as compared to controls (54.5 ± 4.12) (P <0.05). Among the 30 males in cases 25 (83.33%) had microalbuminuria. (P <0.05) microalbuminuria is seen more among smokers (P <0.001). In cases, 26 had a BMI >25 of these 80.76% (n=21) had microalbuminuria. Microalbuminuria is associated with high cholesterol in IHD. Conclusions: The microalbuminuria is significantly associated with in non-diabetic non-hypertensive myocardial infarction. Microalbuminuria is seen at a younger age group in MI. Microalbuminuria is associated with male sex significantly. Microalbuminuria is strongly associated with smoking, high body mass index and high total cholesterol. Microalbuminuria is seen independent of smoking status, BMI, total cholesterol in patients of myocardial infarction.